543. An Integrated Safety Analysis Comparing Once-Daily Doravirine (DOR) to Darunavir+Ritonavir (DRV+r) and Efavirenz (EFV) in HIV-1-Infected, Antiretroviral Therapy (ART)-Naïve Adults. (26th November 2018) - Thompson, Melanie; Orkin, Chloe; Molina, Jean-Michel; Gatell, Jose; Sax, Paul; Cahn, Pedro; Squires, Kathleen; Zhou, Yan; Xu, Xia; Rodgers, Anthony; Kumar, Sushma; Teppler, Hedy; et al.
Abstract: Background: DOR is a novel NNRTI that has shown noninferior efficacy to DRV+r- and EFV-based regimens in phase 3 trials (DRIVE-FORWARD [NCT02275780] and DRIVE-AHEAD [NCT02403674]). A prespecified integrated analysis of those trials plus a completed phase 2 trial (P007; NCT01632345) was performed to evaluate the overall safety and tolerability of DOR. Methods: In this integrated analysis, DOR (100 mg QD) arms from P007, DRIVE-FORWARD, and DRIVE-AHEAD were compared with DRV+r in DRIVE-FORWARD and EFV in P007 and DRIVE-AHEAD for treatment of HIV-1 in ART-naïve adults. The NRTI background included FTC/TDF in P007, ABC/3TC or FTC/TDF in DRIVE-FORWARD, and 3TC/TDF for DOR and FTC/TDF for EFV in DRIVE-AHEAD. The primary safety endpoint was the proportion of participants discontinuing due to adverse events (AEs) through Week 48. Results: A total of 1, 710 treated participants were included in the analysis (table). Similar proportions of DOR− and DRV+r-treated participants, and fewer of those treated with DOR than with EFV discontinued due to AEs (2.5% vs. 3.1%, DOR vs. DRV+r; 2.5% vs. 6.6%, DOR vs. EFV). Drug-related AEs (DRAEs) were similar for DOR (30.9%) and DRV+r (32.1%), and higher for EFV (61.4%). The most common DRAEs (≥10% any group, any grade) were dizziness (4.9%, 1.8%, and 30.7%) diarrhea (4.0%, 12.8%, and 5.7%), and abnormal dreams (3.2%, 0.3%, and 10.6%) for DOR, DRV+r, and EFV, respectively. Higher rates of central nervous system (CNS) AEs were reported for DOR when EFV was the comparator, while similar low rates of CNS AEs were reported for DOR when DRV+r was the comparator. In two prespecified analyses combining the DOR 100-mg arms and EFV arms from P007 and DRIVE-AHEAD, 2.8% vs. 6.1% discontinued due to AEs on the DOR- and EFV-treated arms, respectively, for a treatment difference of −3.4% (95% CI: −6.2, −0.8; P = 0.012); 25.0% vs. 55.9% of participants experienced ≥1 neuropsychiatric AE in DOR and EFV arms, respectively. Conclusion: At Week 48, DOR was generally safe and well tolerated in ART-naïve adults with HIV-1. Statistically significantly lower proportions of DOR- than EFV-treated participants discontinued due to AEs supported by a lower proportion that discontinued due to DRAEs. Those on DOR had fewer CNS AEs compared with those on EFV, and less diarrhea than those on DRV+r. Disclosures: M. Thompson, Merck & Co., Inc.: Research funding to AIDS Research Consortium of Atlanta; no funds to me personally, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally. Bristol Myers Squibb: Research funding to AIDS Research Consortium of Atlanta; no funds to me personally, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally. CytoDyn, Inc.: Research funding to AIDS Research Consortium of Atlanta; no funds to me personally, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally. Gilead Sciences, Inc.: Research funding to AIDS Research Consortium of Atlanta; no funds to me personally, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally. GlaxoSmithKline: Research funding to AIDS Research Consortium of Atlanta; no funds to me personally, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally. Roche Laboratories: Research Funding, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally and Research grant. TaiMed, Inc.: Research Funding, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally and Research grant. ViiV Healthcare: Research Funding, Research funding to AIDS Research Consortium of Atlanta; no funds to me personally. C. Orkin, AbbVie, Abbott, Boehringer Ingelheim, BMS, Gilead, GSK, Janssen, ViiV: Ad Board, Grant Investigator and Research Contractor, Research grant and Research support. J. M. Molina, Merck GIlead ViiV Janssen Teva: Ad Board and Speaker's Bureau, Consulting fee. Gilead Sciences: Grant Investigator, Research support. J. Gatell, Gilead Sciences: Grant and Independent Contractor, Consulting fee and Educational grant. Janssen: Grant and Independent Contractor, Consulting fee. ViiV Healthcare: Grant and Independent Contractor, Consulting fee. MSD: Grant and Independent Contractor, Consulting fee. P. Sax, Gilead: Consultant and Grant Investigator, Consulting fee, Grant recipient and Research grant. ViiV Healthcare: Consultant and Grant Investigator, Consulting fee, Grant recipient and Research grant. Merck: Consultant and Grant Investigator, Consulting fee, Grant recipient and Research grant. Janssen: Consultant, Consulting fee. BMS, Gilead, Merck, GSK/ViiV: Grant Investigator, Grant recipient and Research grant. P. Cahn, Abbvie: Grant, Research grant. Merck: Grant, Advisory Board. ViiV Healthcare: Grant, Advisory Board. K. Squires, Merck & Co., Inc.: Ad Board, Ad Board. Gilead Sciences: Grant, Ad Board. VIIV: Ad Board, Ad Board. Bristol Myers Squibb: Ad Board, Ad Board. Janssen: Ad Board, Ad Board. Y. Zhou, Merck & Co., Inc.: Employee, Salary. X. Xu, Merck & Co., Inc.: Employee, Salary. A. Rodgers, Merck & Co., Inc.: Employee and Shareholder, Salary. S. Kumar, Merck & Co., Inc.: Employee and Shareholder, Salary. H. Teppler, Merck & Co., Inc.: Employee and Shareholder, Salary. E. Martin, Merck & Co., Inc.: Employee and Shareholder, Salary. G. Hanna, Merck & Co., Inc.: Employee and Shareholder, Salary. C. Hwang, Merck & Co., Inc.: Employee and Shareholder, Salary.